An Exploratory Study of Employers' Attitudes Towards a Clinical Doctorate in Genetic Counseling. Issue 1 (14th July 2015) - Valverde, Kathleen; Mueller, Rebecca; Paciotti, Breah; Conway, Laura
Abstract: Creation of an advanced degree in genetic counseling has been considered since the early 1980s. The Genetic Counseling Advanced Degree Task Force (GCADTF) was convened in 2012 to formally explore the potential suitability of a clinical doctorate (ClinD), though employer perspectives of advanced training were not part of the discussion. The conclusion of this group was that the field was not ready to move to an entry‐level clinical doctorate at this time but that further education and research among other stakeholders was necessary (Nagy et al. 2014). In this study, we describe employers' perspectives on developing a clinical doctorate in genetic counseling based upon thirty audio‐recorded semi‐structured phone interviews that were transcribed verbatim and qualitatively analyzed. Overall, employers expressed concerns regarding the economic viability of ClinD training but envisioned expanded roles for genetic counselors (especially in areas of education and research) and enhanced credibility. While some employers reported that they would provide flexibility and tuition assistance for acquisition of a ClinD, for many employers, support was contingent on perceived value of the degree. Some employers were not clear about the difference between a ClinD and a PhD, suggesting that there is a need for educating employers about advanced degree options for the genetic counseling field. Future research could include investigating employer attitudes about market needs, envisioned roles, and compensation formulas for counselors with a ClinD or other forms of advanced training.